The Effect of Fuel Price Fluctuations, Exchange Rates, and Profitability on Stock Returns and Inflation as Intervening Variables - Satoto, Eko Budi (Universitas Pendidikan Nasional, 2023)
This study aims to analyze the impact of fuel price fluctuations, exchange rates, and profitability on inflation and stock returns. The study employs statistical analysis utilizing SEM techniques and is tested using Smart PLS version 3.0. The study reveals that Fuel price fluctuations have no effect on Inflation. The direction of the relationship between Exchange Rate and Inflation is negative. Profitability has no effect on Inflation. Fuel price fluctuations have no effect on stock returns. Exchange rate has a significant effect with a positive direction on stock returns. Profitability has no direct effect on stock returns. Inflation has a significant effect directly with a negative direction on Stock Returns. Exchange rate has no effect on stock returns through inflation as an intervening variable. Profitability has a significant effect with a positive direction on stock returns through inflation as an intervening variable. The novelty in research is inflation as an intervening variable. Investors are advised that fluctuations in fuel prices and inflation rates need not be a primary concern in their investment decisions. Instead, the focus should be on assessing the potential impact of these factors on company profits. Consequently, investors should emphasize monitoring stock returns periodically while also taking into account variables that could influence a company's stock returns. The study is limited in its scope by examining only three independent variables—Fuel Price Fluctuations, Exchange Rates, and Profitability. Additionally, the research is confined to the period from 2013 to 2017.